In vivo characterization of physiological and metabolic changes related to isocitrate dehydrogenase 1 mutation expcression by multiparametric MRI and MRS in a rat model with orthotopically grafted human‐derived glioblastoma cell lines. (17th February 2021) - Clément, Alexandra; Doyen, Matthieu; Fauvelle, Florence; Hossu, Gabriela; Chen, Bailiang; Barberi‐Heyob, Muriel; Hirtz, Alex; Stupar, Vasile; Lamiral, Zohra; Pouget, Celso; Gauchotte, Guillaume; Karcher, Gilles; et al.
Abstract : The physiological mechanism induced by the isocitrate dehydrogenase 1 ( IDH1 ) mutation, associated with better treatment response in gliomas, remains unknown. The aim of this preclinical study was to characterize the IDH1 mutation through in vivo multiparametric MRI and MRS. Multiparametric MRI, including the measurement of blood flow, vascularity, oxygenation, permeability, and in vivo MRS, was performed on a 4.7 T animal MRI system in rat brains grafted with human‐derived glioblastoma U87 cell lines expressing or not the IDH1 mutation by the CRISPR/Cas9 method, and secondarily characterized with additional ex vivo HR‐MAS and histological analyses. In univariate analyses, compared with IDH1−, IDH1+ tumors exhibited higher vascular density ( p < 0.01) and better perfusion ( p = 0.02 for cerebral blood flow), but lower vessel permeability ( p < 0.01 for time to peak (TTP), p = 0.04 for contrast enhancement) and decreased T 1 map values ( p = 0.02). Using linear discriminant analysis, vascular density and TTP values were found to be independent MRI parameters for characterizing the IDH1 mutation ( p < 0.01). In vivo MRS and ex vivo HR‐MAS analysis showed lower metabolites of tumor aggressiveness for IDH1+ tumors ( p < 0.01). Overall, the IDH1 mutation exhibited a higher vascularity on MRI, a lower permeability, and a less aggressive metabolic profile. These MRI features may prove helpful to better pinpoint the physiological mechanisms induced by this mutation. Abstract : The aim of this preclinical study was to characterize IDH1 mutation through in vivo multiparametric MRI and MRS. Overall, the IDH1 mutation exhibited a higher vascularity on MRI, a lower permeability, and a less aggressive metabolic profile. These MRI features may prove helpful to better pinpoint the pathophysiological mechanisms induced by this mutation.